O prazer do terror em psicanálise - Rocha, Victor Moura (2013)
In the present study sought with the aid of psychoanalysis, more specifically the Freudian production, to study the relationship between terror and pleasure that is associated with it. To accomplish this it took a course in some of the most important psychoanalytic concepts such as infantile sexuality, narcissism, sexual and narcissistic pleasure, masochism, sadism and aggressiveness. In addition, this work which was born of a worry regarding the fascination and revulsion of terror that exists in our society, searching the relationship between the natural aggressiveness of human and prohibitions on exercise them freely, and why this dynamic has intimate relation with the problem of pleasure felt by humans against terror. This study found evidence in the literature that suggest that in fact, this aggressiveness that cannot be satisfied directly, can be through the terror and uses it as a means of libidinal satisfaction, thus serving as an ally of civilization. Besides this, other issues that bind terror pleasure are also worked, such as narcissism, masochism and sadism.